Neutralizing capacity of antisera obtained by immunization with Bothrops alternatus venom blocked in its metalloproteinases - López, Gisela Lumila (2019)
Specific treatment for snake bite accidents with antivenoms, obtained from immunized animals, is the only recommended therapy. Bothropic intoxication is characterized by proteolytic, coagulant and hemorrhagic effects that induce local tissue damage and systemic alterations that could lead to death. Snake venom metalloproteinases, zinc- dependent, play a relevant role in the pathogenesis of intoxication. They provoke a disruption of the hemostatic system, restricting their use as immunogen in high doses. In previous work, it was demonstrated that is it possible to immunize mice with high doses of Bothrops alternatus venom (BaV) neutralized with disodium salt of ethylenediaminetetraacetic acid (Na2EDTA) avoid of hemorrhagic lesions and then animals reported higher antibodies titer. The present study was performed to test the neutralizing ability of sera obtained from animals treated whit venom-Na2EDTA, and evaluate the effect of this immunogen on pulmonary parenchyma. Groups of 5 Balb/c mice were immunized subcutaneously with BaV, or BaV/Na2EDTA emulsified with Freund?s Adjuvant (complete first and incomplete-booster). On day 50 serums were collected for neutralization assays: proteolytic activity on azocasein, phospholipase activity on erythrocytes and thrombine-like activity on citrated plasma. Animals were sacrificed and lungs removed for histological analysis (hematoxylin-eosin). The results showed that the capacity of neutralize each of one of the three enzyme activities assayed was significantly higher (p <0.05) by the serum obtained from animals immunized with BaV/Na2EDTA. Histological analysis showed that the pulmonary parenchyma from immunized mice with BaV was significantly affected (pneumonitis, p <0.05), in respect to those were BaV/Na2EDTA treated. Results demonstrated that the BaV/Na2EDTA immunogen has a lower organic impact with respect to BaV and, at the same time, providing a serum with high neutralizing capacity.